A contribution to the validation of the Italian version of the work-related quality of life scale - Garzaro, Giacomo; Clari, Marco; Donato, Francesca; Dimonte, Valerio; Mucci, Nicola; Easton, Simon; Van Laar, Darren; Gatti, Paola; Pira, Enrico (La Medicina del Lavoro, 2020)
Background: Quality of working life has been shown to play a key role in reducing strain inside and outside the workplace, supporting the fulfillment of workers’ wellbeing and increasing workforce productivity. Van Laar et al. in 2007 developed the Work-Related Quality of Life (WRQoL) scale that was applied to several different work environments and translated into nine languages. Objectives: We aimed to test and validate an Italian version of the WRQoL scale. Methods: A cross-sectional design was conducted to collect a sample of healthcare professionals (N=430) in 8 hospitals in the Northwest of Italy. Internal consistency of each scale was tested through Cronbach’s alpha. A Confirmatory factor analysis was performed. Independent samples t-tests and ANOVA were performed to determine whether the scores on the subscales differed according to various socio-demographic variables. Results: A seven factors structure was confirmed (Control at work; General well-being; Home-work interface; Stress at Work; Job and career satisfaction; Working conditions; Employee Engagement; χ2=682.453, p